2021
DOI: 10.1140/epjds/s13688-021-00299-2
|View full text |Cite
|
Sign up to set email alerts
|

Putting human behavior predictability in context

Abstract: Various studies have investigated the predictability of different aspects of human behavior such as mobility patterns, social interactions, and shopping and online behaviors. However, the existing researches have been often limited to a single or to the combination of few behavioral dimensions, and they have adopted the perspective of an outside observer who is unaware of the motivations behind the specific behaviors or activities of a given individual. The key assumption of this work is that human behavior is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3
2

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…Several studies have used mobile phone data to study mobility and migration patterns in developing countries specifically [ 4 , 55 57 ]. Yet despite multi-modal data from different contexts improving prediction accuracy [ 58 ], no research, to the best of our knowledge, has attempted to use this data combined with mobile money transactions to assess the characteristics and potential social and economic consequences of urban migration to the migrant themselves; nor examined the factors that implicate the deprivation level of where people migrate to within urban settings. While academic research on mobile money and migration has previously focused on the rural communities left behind, one prior work [ 59 ] has shown that social networks in a destination location can strongly impact the success of a migration.…”
Section: Related Workmentioning
confidence: 99%
“…Several studies have used mobile phone data to study mobility and migration patterns in developing countries specifically [ 4 , 55 57 ]. Yet despite multi-modal data from different contexts improving prediction accuracy [ 58 ], no research, to the best of our knowledge, has attempted to use this data combined with mobile money transactions to assess the characteristics and potential social and economic consequences of urban migration to the migrant themselves; nor examined the factors that implicate the deprivation level of where people migrate to within urban settings. While academic research on mobile money and migration has previously focused on the rural communities left behind, one prior work [ 59 ] has shown that social networks in a destination location can strongly impact the success of a migration.…”
Section: Related Workmentioning
confidence: 99%
“…This immediately suggests an ML approach consisting of two steps: collecting examples of sensor recordings annotated with context information and then using this data to learn a map between the two that generalizes to unseen situa-tions. A recent investigation of learning techniques for PCR carried out on the SmartU-nitn2 data shows that indeed automated recognition can be achieved with some degree of success [14,15].…”
Section: Continually Evolving Context Recognitionmentioning
confidence: 99%
“…Figuring out what predictors and architectures are best suited for this task will likely involve borrowing ideas from activity recognition and related areas, while mixing in strategies for dealing with specific aspects of PCR, such as incrementality and support for interaction, which are critical for lifelong alignment (as discussed below). Another important element is that the personal context is inherently structured [15], in the sense that its various aspects are correlated -e.g., a person's activity is strongly influenced by the location that she is in -and constrained by the structure of the context knowledge graph. This hints at the need for developing or repurposing structure-aware predictors.…”
Section: Continually Evolving Context Recognitionmentioning
confidence: 99%
“…1 The app used for the data collection is called iLog [18,17]. The SU data set has been used in a large number of case studies, see, e.g., [19,20]. SU has been collected from one hundred and fifty-eight university students over a period of four weeks.…”
Section: Case Studymentioning
confidence: 99%